‘Authentic’ Assessment of Clinical Competence: Where We Are and Where We Want to Go in Future - Nurunnabi, Abu Sadat Mohammad; Rahim, Riffat; Alo, Dilara; Muqueet, Md Abdul; Rahman, Hasan Hafizur; Jahan, Nelema; Talukder, Mohammad Abu Sayeed; Tapu, Thanadar Tamjeeda (Mugda Medical College Journal, 2023)
The assessment of clinical competence is one of the most difficult tasks facing medical education. Teaching and assessment need to be meaningful for the students and their relevance in real life context and challenges should be apparent. Ideally, assessment tasks should require students to use the same competencies, or combinations of knowledge, skills, and attitudes that they need to apply in their future professional life. However, for the medical teachers of our country the term “authentic assessment” is very new, as most of them are very stick to traditional assessment while running a course or training students in different medical colleges. Clinical competence is an extremely complex construct and one that requires multiple, mixed, and higher order methods of assessment. As we have experienced a recent pandemic situation, it seems that plenty of questions remain in relation to clinical competence assessment in medical colleges for now and near future. In authentic assessment, students will go beyond the textual reproduction of fragmented and low order content and move towards understanding, establishing relationships between new ideas and previous knowledge, linking theoretical concepts with everyday experience, deriving conclusions from the analysis of data, allowing them to examine both the logic of the arguments present in the theory, as well as its practical scope. That is why we are moving away from traditional, limited test formats to new, more complex, yet innovative, mixed methods of ‘authentic’ assessment – from faculty observation ratings and paper-and-pencil examinations to online MCQ tests, SBA questions, experimentation with advanced OSPE and OSCE, and project-based assessment supplemented with clinical reasoning. These moves are expected to bring not only several challenges but also great educational rewards for the measurement and advancement of clinical competence among students. We would like to continue to work on those progressions. Mugda Med Coll J. 2023; 6(1): 37-43